PENERAPAN STRATEGI PEMBELAJARAN TEMATIK MUATAN PELAJARAN ILMU PENGETAHUAN SOSIAL - Latifah Dwi Utami; Dhi Dhi Bramasta2 Bramasta (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Research through the program Assignment Lecturer in the School (PDS) in Class IV Primary School Universitas Muhammadiyah Purwokerto (SD UMP) goes well. Learning implemented in class IV Zaid Bin Tsabit Primary School Universitas Muhammadiyah Purwokerto. learning strategies applied Learning Strategies to Increase Thinking Ability (SPPKB). There are six stages in SPPKB applied in the present study. Starting with the orientation phase, the tracking stage, the stage of confrontation, the stage of inquiry, accommodation phase and ended the transfer phase. Stages of inquiry is the most important stages. At this stage the students learn to think real. Learners are encouraged to solve problems encountered. Some learners difficulties in the learning process-oriented thinking and invention concept. The issue presented in a matter can not be solved learners. Learning media in the form of animated short films about religious diversity effectively evoke the imagination inspires learners. Application of learning strategy SPPKB able to improve the ability of thinking and invention concepts and learners are able to solve problems that served learning materials. When students were asked to argue, invented the concept of the learning process has been able to express their opinions well. SPPKB strategy implementation can provide a solution to students who have been experiencing difficulties in the learning process oriented thinking and invention concepts and problem solving. Keywords: Thematic Learning Strategies, Social Sciences